Report on lecture by Professor Dr. Bjarne W. Olesen on indoor environment - health - comfort and productivity and the European Energy Performance of Building Directive (EPBD) - Leong, Siew Meng (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/